Structure-Activity Relationship Study on the Ethyl p-Methoxycinnamate as an Anti-Inflammatory Agent - Ismiarni Komala; Supandi Supandi; Nurhasni Nurhasni; Ofa Suzanti Betha; Eka Putri; Syarifatul Mufidah; Muhammad Fikry Awaludin; Mida Fahmi; Muhammad Reza; Nurkhayati Putri Indriyani (Indonesian Journal of Chemistry, 2018)
Ethyl p-methoxycinnamate (EPMC) (1) has been isolated as a major compound from the rhizome of Kaempferia galanga together with the other compound ethyl cinnamate (2). As reported in the literature, EPMC (1) exhibited a significant in vitro and in vivo anti-inflammatory activity. In this research, we investigated the anti-inflammatory activity of compounds 1 and 2 by using anti-denaturation of heat bovine serum albumin (BSA) method. In order to analyze active sites that are responsible for the anti-inflammatory activity, therefore, it is necessary to conduct structural modification of EPMC (1). The structural modification was performed through re-esterification reaction by using conventional and assistance of the unmodified microwave oven. Evaluation of the results of the bioassay indicated that the ester and methoxy functional groups of EPMC (1) play an important role for the anti-inflammatory activity.